2010
DOI: 10.1177/003335491012500219
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Gender Dynamics and Engaging Men in HIV Programs: Lessons Learned from Horizons Research

Abstract: In the field of human immunodeficiency virus (HIV) prevention, there has been increasing interest in the role that gender plays in HIV and violence risk, and in successfully engaging men in the response. This article highlights findings from more than 10 studies in Asia, Africa, and Latin America--conducted from 1997 through 2007 as part of the Horizons program--that have contributed to understanding the relationship between gender and men's behaviors, developing useful measurement tools for gender norms, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
154
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(165 citation statements)
references
References 23 publications
(41 reference statements)
9
154
1
1
Order By: Relevance
“…Otras razones podrían ser la violencia de género mediante el abuso sexual, el menor acceso a la información que tienen las mujeres y la necesidad de mejora de sus habilidades para la negociación del sexo protegido que exponen al riesgo de infección a las mujeres. Precisamente, existen estudios muy actuales en los que se ha abordado la influencia de las dinámicas de poder y los roles de género en la pareja sobre el riesgo de infección de VIH [21][22][23] . Por tanto, se precisa el desarrollo de investigaciones y la implantación de programas de prevención del VIH y enfermedades de transmisión sexual en estos países que tengan en cuenta estos factores y se focalicen en esta población.…”
Section: Discussionunclassified
“…Otras razones podrían ser la violencia de género mediante el abuso sexual, el menor acceso a la información que tienen las mujeres y la necesidad de mejora de sus habilidades para la negociación del sexo protegido que exponen al riesgo de infección a las mujeres. Precisamente, existen estudios muy actuales en los que se ha abordado la influencia de las dinámicas de poder y los roles de género en la pareja sobre el riesgo de infección de VIH [21][22][23] . Por tanto, se precisa el desarrollo de investigaciones y la implantación de programas de prevención del VIH y enfermedades de transmisión sexual en estos países que tengan en cuenta estos factores y se focalicen en esta población.…”
Section: Discussionunclassified
“…6,7 Qualitative research suggests that pervasive norms about how males and females are supposed to behave can affect sexual risk behaviours; for example, young women may be unwilling to carry condoms or request their use because of the implication that they are sexually promiscuous.…”
Section: 2mentioning
confidence: 99%
“…[3][4][5][6][7][8] Gendered power imbalances in sexual relationships may constrain young women's ability to negotiate safe and pleasurable sex. A US cross-sectional study showed that women with high levels of power in their intimate relationships were five-fold as likely as women with low levels to report consistent condom use, after controlling for sociodemographic and psychosocial variables.…”
Section: 2mentioning
confidence: 99%
See 2 more Smart Citations